Pembuatan Aplikasi E-Office Di PT. Almega Sejahtera Untuk Mendukung Kegiatan Perkantoran Berbasis Web Menggunakan FI Framework - Andrevianto, Devanda; , Umi Fadlilah, S.T., M.Eng (2015)
PT. Almega Sejahtera is the only agent in Indonesia which is engaged in the sale of laboratory equipment products brand Mettler Toledo and laboratory equipment for pharmaceutical brand Erweka. Each company has its own policies to implement the business process each - each. Business processes within a company is the most important part in the streamline and streamline every process that occurs in a company, especially in the delivery process and storage of data or documents. Business process in PT. Almega Prosperous still fairly manual for that need a system that can be used for shipping or storage of data that is automation. Applications that will be used in PT. Prosperous Almega the e-office. E-office using the programming language PHP open source framework using FI Framework which can adjust the library that will be called into the application, and using a MySQL database, created in the form of a website. In the test phase, to provide an assessment conducted in PT. Almega Prosperous Semarang with respondents from the manager (admin), Personnel and Employee to demonstrate these applications directly and via a questionnaire respondents provide an assessment that has been made. The existence of this application the office activities are becoming increasingly fast, easy and efficient. This application is also supported by the submissions feature peer to peer inter office memos, announcements feature wherein the feature will be up to date if there is new information, permission to leave the features can be done online which can facilitate the employees and personnel to take leave from, is entitled to take a leave permit decision ie manager (admin). This application is also supported with additional features tools - tools of office equipment, office where co-workers can borrow tools online.